Virtual Instructional Packages and Pre-Service Language Teachers’ Communicative Skills: Empirical evidence from Nigerian Colleges of Education. - FALOYE , Bankole Olagunju; Obateru, Oluwatoyin Tolu (Archives of Business Research, 2021)
The study investigated the effect of virtual instructional tools on the learning outcomes of pre-service English language teachers in Nigerian Colleges of Education. The rationale of the study was hinged on the premise of virtual instructional adaptation in a post-OVID-19 era. The design for the study was a two- group pre-test post-test quasi-experimental design. The research design comprised pretest and post-test observations, treatment with virtual instruction and normal instruction in a non-virtual space. Using multistage sampling strategy, 100 samples were randomly selected from two Colleges of Education in Southwest Nigeria. The experimental and controls groups consisted of 50 samples each comprising 25 females and 25 males. The instruments for the study were validated achievement tests and marking guides including a test-retest reliability study with a reliability coefficient of 0.87 which was considered as moderately high for the reliability of the instruments. Two null hypotheses were raised and tested at 0.05 levels of significance using Two- Way ANOVA as statistical tools. The findings revealed that there was significant effect of virtual instructional tools on pre-service English language teachers’ learning outcomes using the pre-test mean scores and post-test mean scores. Also, the findings showed that there was significant gender effect of virtual instructional tools on the virtual learning outcomes of pre-service English language teachers’ communicative skills in English. Pedagogical implications of the findings in respect to virtual instructional tools in a post-COVID-19 era were highlighted and suggestions preferred towards enhancing pedagogical and communicative competencies of pre-service English teachers in Nigerian Colleges of Education.